EMPOWERMENT OF PELANGI GUNUNG SULING WOMAN FARMERS GOUP (KWT) IN PROCESSING COFFEE SKIN WASTE INTO CASCARA - panglima, Linar Humaira; Jannah, Asmanur; Srikandi, Srikandi (Universitas Djuanda, 2021)
Bogor Regency in one of the coffee producers in west Java, including coffee from Barengkok Village, Leuwiliang District, Bogor Regency. So far, farmers in post-harvest processing of coffee cherries only process coffee beans, while the skin is removed so that it becomes waste that is not utilized. Whereas from the coffee skin, there are many ingredients that are very beneficial for health, including rich in antioxidants, but the knowledge and skills of farmers in processing coffee bean waste are still low, so there is a need for education for the people of Barengkok Village. The purpose of this activity is to increase the knowledge and skills of the Women Farmers Group (KWT) through education and training in processing coffee bean waste into Cascara as a health drink, so that it has economic value. The method of implementing this activity uses counseling, demonstrations and training on Cascara production, production management and product marketing strategies. Partners in this activity were the Pelangi Gunung Suling Women Farmer Group (KWT), totaling 18 people. To see the success of the program, it was carried out through the pretest and posttest analyzed by quantitative descriptive. The results of the activity showed that there was an increase in partner knowledge in processing coffee skin waste from unknowing to 94.4% knowing and understanding, the participants were very enthusiastic about participating in this empowerment activity as seen from the number of attendees who were 100% present from beginning to end. Coffee skin waste can be of economic value through processing health drinks, thus making it a new business opportunity.